Tuberculosis Notification Surveillance System Evaluation in Bulilima District Zimbabwe, 2020 - Mutizwa Thomas Mupedziswa; Rudo Chikodzore; Addmore Chadambuka; Tsitsi Patience Juru; Mujinga Karakadzai; Notion Tafara Gombe; Chukwuma David Umeokonkwo; Mufuta Tshimanga (Journal of Interventional Epidemiology and Public Health)
Introduction: The World Health Organisation (WHO) recommends the detection of 90% of WHO's estimated TB incidence. In 2020 Bulilima District detected 31% of Zimbabwe`s estimated incidence thereby failing to meet the WHO detection target. Low TB case detection negatively impacts patient management and TB programming. We assessed TB surveillance system attributes and determined the reasons for low TB case notification in Bulilima District. Methods: We conducted a descriptive crosssectional study among 91 health workers involved in TB programming in all 16 health facilities in Bulilima District using updated US CDC guidelines for evaluation of the public health surveillance system, including document/records review and secondary data analysis. District Medical Officer, District Nursing Officer, District Pharmacist, District Environmental Health Technician, District Health Information Officer, District Laboratory Technician, Community Nurse, District Health Promotion Officer and the TB focal person were recruited as key informants. We used questionnaires to assess knowledge, a checklist to assess system attributes, and a key informant interviewer guide to assess reasons for low notification. We analyzed quantitative data using Epi Info 7 to generate frequencies and proportions and qualitative data was analysed manually. Results: All health facilities submitted quarterly reports timely and 46.2% (42/91) of health workers demonstrated good knowledge of the surveillance system. The surveillance system was simple, stable, acceptable, and useful. The district had one TB diagnostic laboratory providing service to the 16 health facilities and manned by one microscopist. This was the reason for low TB notification as results are often delayed or never received. Conclusion: The surveillance system was stable, simple, and acceptable and generated information which was used for public health actions. The district had limited TB diagnostic capacity which contributed to the low TB notification. We recommended filling of Laboratory Technicians and Laboratory Scientist posts at the diagnostic center.